Characteristics of Parent–Child Interactions: A Systematic Review of Studies Comparing Children With Primary Language Impairment and Their Typically Developing Peers. (February 2015) - Blackwell, Anna K. M.; Harding, Sam; Babayiğit, Selma; Roulstone, Sue
The importance of parent–child interaction (PCI) for language development has been well established. This has led many speech and language therapy (SLT) interventions to focus on modifying PCI as a means to improving children's early language delay. However, the success of such programs is mixed. The current review compares PCI, observed in naturally occurring contexts, with preschool children with language delay and age- or language-matched typically developing (TD) controls. A systematic review of the literature searched 10 databases for studies using a case-control design and extracted data concerning participants, matching, selection, design, assessments, measures, findings, statistics, and bias. Quality appraisal used the Critical Appraisal Skills Programme case-control checklist. The search identified 17, 824 articles, which were reviewed against exclusion criteria. The final review included 9 studies, which were diverse in terms of matching, delay criteria, and PCI measure. A narrative synthesis was conducted. The evidence for PCI differences between children with language delay and TD peers was limited and any suggestion that parents were less responsive could be attributed to limited language skills of children with language delay. The findings question the assumption that communicative environments of children with language delay are different, although the evidence is from a small sample of children from middle-class families. Children with language delay may instead be less able to learn from their environment. The review highlights the gap in understanding the relationship between parent and child language use during PCI. The need for further, longitudinal research is emphasized, including children ranging in type and severity of delay, across diverse socioeconomic backgrounds.